2019
DOI: 10.3390/catal9100810
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Microstructure and Deactivation Effects on Commercial NiMo/γ-Al2O3 Catalyst through Aberration-Corrected Scanning Transmission Electron Microscopy

Abstract: Atom-resolved microstructure variations and deactivation effects on the commercial NiMo/γ-Al2O3 catalysts were revealed by aberration-corrected scanning transmission electron microscope (Cs-STEM) equipped with enhanced energy dispersive X-ray spectroscopy (EDS). Structural information parallel to and vertical to the electron beam provides definitive insight toward an understanding of structure–activity relations. Under the mild to harsher reaction conditions, “fragment” structures (like metal single atoms, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…It has been reported that compounds containing single oxygenated groups such as phenol tend to produce less coke when compared to guaiacol or veratrole due to condensation reactions . He et al also reported that coke deposited on the metal site of the NiMo/γ–Al 2 O 3 catalyst can be removed by the self-cleaning process by the active H 2 spillover . Furthermore, the coke deposited over the metal sulfide active sites can be partially removed by H 2 during reduction, whereas the coke deposited on carbon support pore channels are difficult to eliminate .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that compounds containing single oxygenated groups such as phenol tend to produce less coke when compared to guaiacol or veratrole due to condensation reactions . He et al also reported that coke deposited on the metal site of the NiMo/γ–Al 2 O 3 catalyst can be removed by the self-cleaning process by the active H 2 spillover . Furthermore, the coke deposited over the metal sulfide active sites can be partially removed by H 2 during reduction, whereas the coke deposited on carbon support pore channels are difficult to eliminate .…”
Section: Resultsmentioning
confidence: 99%
“…50 He et al also reported that coke deposited on the metal site of the NiMo/γ−Al 2 O 3 catalyst can be removed by the self-cleaning process by the active H 2 spillover. 51 Furthermore, the coke deposited over the metal sulfide active sites can be partially removed by H 2 during reduction, whereas the coke deposited on carbon support pore channels are difficult to eliminate. 52 In our case, it is noted that the percentage of coke deposited on the catalyst at the end of each cycle decreased after hydrogen reduction before being recycled in the next cycle, probably due to the partial hydrogenation of the poorly organized carbon formed close to the metal sites due to hydrogen spillover (Figure 5).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…As a result, EDX has been widely applied for the determination of SACs together with HAADF-STEM. [72][73][74] 2.5 Electron energy loss spectroscopy EELS is utilized to investigate the chemical composition, stoichiometry, energy levels and electronic structure of catalysts. 75,76 EELS requires electrons to strike the catalyst surface, so it is conducted on TEM or STEM.…”
Section: Energy Dispersive X-ray Spectroscopymentioning
confidence: 99%
“…As a result, EDX has been widely applied for the determination of SACs together with HAADF-STEM. 72–74 …”
Section: Characterization Techniques For Evidence Of Single Atoms In ...mentioning
confidence: 99%
“…The development of microscopy technology contributes to analyzing the surface property of the deactivated catalysts. The major active phases of hydrotreating catalyst are MoS 2 , NiMoS, and CoMoS phases, which have been investigated by scanning tunneling microscopy (STM). atom-resolved microstructure variations, and the deactivation effects on NiMo/Al 2 O 3 catalyst have been represented by aberration-corrected scanning transmission electron microscope (Cs-STEM) . It revealed that MoS 2 nanoslabs got longer and thinner under mild to harsh reaction conditions, which led to a reduction in the number of active sites and a significant decrease in activity.…”
Section: Introductionmentioning
confidence: 99%